The Effects of the Trade of Futures Contracts on the Volatility of the Spot Market : Evidence From Bursa Malaysia - Habonimana, Robert (2011)
The effects of the trade of futures contracts on the underlying spot market volatility and its repercussions, is still debated among financial and economic practitioners. This study investigates the impact of the inception of the trade of futures contracts on the volatility of the underlying Malaysian spot market. It also examines the direction of the trade of futures on the volatility of the spot market. Daily closing prices of the KLCI-30 index were utilized to analyse the degree to which the trade in futures contracts have affected the underlying Malaysian spot prices volatility subsequent to its introduction on 15th December 1995. To examine the direction and the degree to which the volatility of the underlying Malaysian spot market changes in accordance to the start of the trade of futures contracts, we use two GARCH family models namely GARCH (1, 1) and EGARCH (1, 1); a Vector Autoregression model as well as a Granger causality test. Research findings reveal that the inception of the trade of futures contracts has led to the decrease of the underlying stock market volatility. It also reveals that recent news information is slowly incorporated into prices and old news has a high persistence effect on the changes of price. The presence of leverage effect is also observed and implies that the stock price volatility increase when there is occurrence of market decline. The lead-lag relationship analysed under the VAR model shows that the futures trading activities lead the underlying stock market volatility. This is proved by the Granger causality which reveals that the futures trading activities cause the volatility of the underlying stock market. This paper will be helpful to financial managers, regulators and policymakers in the Malaysian emerging market as futures contracts are important hedging instruments in financial markets. It will enable them to examine whether more regulations are needed or not in the aim of providing market efficiency.